Santa Clara Theatre. - Gordon, John C. (photographer):::Creator::::::::::::
Exterior view of the Santa Clara Theatre, located in Santa Clara, California. Marquee reads ' "One Third of a Nation" also Gordon Keith Kiddie Revue.' Photograph shows an unknown man standing in front of the theatre next to a car and a female theatre employee in the ticket booth.